Answer :

**Given:**

f(x) = mx^{2} – x + 1

(x + 1) is factor of f(x)

**Concept Used:**

The **factor theorem** states that a polynomial has a **factor** if and only if it is a root.

Or

If (x – a) is a factor of f(x), then f(a) = 0

**Explanation:**

x + 1 = 0

x = –1

f(–1) = m.(–1)^{2} + 1 + 1 = 0

m + 2 = 0

m = –2

m^{2} = (–2)^{2} = 4

Hence, m^{2} = 4

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

When a polynomialRS Aggarwal - Mathematics

Find all the zeroRD Sharma - Mathematics